Understanding the dual burden of physical and neurodegenerative multimorbidity on depressive symptoms in older black adults - Seungjong Cho; Tyrone C. Hamler (Discover Public Health)
Abstract Background There are notable research gaps regarding physical and neurodegenerative multimorbidity and depressive symptoms, particularly among older Black adults. Aim Guided by cumulative advantage/disadvantage theory, this study examines the association between physical and neurodegenerative multimorbidity and depressive symptoms within this population. Methods This study analyzed a sample from the 2018 Health and Retirement Study (N = 812; age 65 +). Physical multimorbidity included diagnoses of seven chronic conditions: high blood pressure, diabetes, cancer, lung disease, heart disease, stroke, and arthritis. Neurodegenerative multimorbidity covered Alzheimer’s disease and other memory impairments. Depressive symptomatology was measured with the eight-item CES-D scale. Results Negative binomial regression analyses revealed that higher physical and neurodegenerative multimorbidity were both significantly associated with increased depressive symptoms. Additionally, lower income was associated with higher depressive symptoms. Discussion These findings underscore the urgent need for targeted mental health interventions for older Black adults experiencing multimorbidity. Addressing depressive symptoms in this population requires training health care professionals to recognize and manage complex comorbidities and fostering collaboration between providers specializing in physical and neurodegenerative conditions. As this population continues to age, integrating mental health care into routine chronic disease management will be critical for improving overall well-being. Future research should explore intervention strategies that mitigate the psychological burden of multimorbidity and promote equitable health outcomes.